2005
DOI: 10.1115/1.2039111
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nucleation With Artificial Cavities

Abstract: Bubble incipience in artificial cavities manufactured from silicon has been studied using gas nucleation and pool boiling. Moderately wetting water and highly wetting ethanol have both been used as the bulk fluid with cylindrical cavities, as well as those with a triangle, square, and rectangle shape cross section. Nominal cavity sizes range from 8to60μm. The incipience conditions observed for water using both gas nucleation and pool boiling suggest that bubble initiation originates from a concave meniscus. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The results of Griffith and Wallis37 also showed that a smaller cavity requires a higher nucleation temperature as well. Qi and Klausner44 have also observed that the wall superheat is larger when size of cavity is smaller. However, the gas entrapment mechanism by Bankoff30 suggested that a cavity is filled with liquid if its cone angle is larger than the contact angle of the liquid on the surface.…”
Section: Discussionmentioning
confidence: 92%
“…The results of Griffith and Wallis37 also showed that a smaller cavity requires a higher nucleation temperature as well. Qi and Klausner44 have also observed that the wall superheat is larger when size of cavity is smaller. However, the gas entrapment mechanism by Bankoff30 suggested that a cavity is filled with liquid if its cone angle is larger than the contact angle of the liquid on the surface.…”
Section: Discussionmentioning
confidence: 92%
“…40,41 The volume of air trapped varies with the geometry and wettability of the cavity as well as the fluid dynamics of microgripper immersion. 42 When the bubble diameter is less than the capillary length of water, ∼2.7 mm at room temperature, the Laplace pressure is greater than the hydrostatic pressure. Under this condition, the protruding bubble is approximated as a spherical cap with a height h and base radius r b .…”
Section: Resultsmentioning
confidence: 99%
“…These formulations indicate that any cavity with an advancing water contact angle above 90°will always capture a bubble, regardless of depth, but it is noted that the phenomenon is both complex and dynamic and continues to be an unsolved challenge. 42 The requirement for a cylindrical cavity to be an active nucleation site has been shown, but the necessary condition for boiling yields fewer possible aspect ratios than eqn (4). 59 However, by designing the cavity to be an active nucleation site, new bubbles to be captured and controlled can be nucleated by an external heating source, e.g.…”
Section: Microgripper Designmentioning
confidence: 99%
“…It is important to note that during boiling, cavities may still settle after activation to produce bubbles, resulting in a rapid rise in local surface temperature. Qi and Klausner [27] studied the heterogeneous nucleation of artificial cylindrical cavities fabricated on silicon substrates, with diameters ranging from 8 to 60 µm and depths of 45 µm, and observed that bubble nucleation during the boiling process showed an intermittent pattern, with the cavities experiencing a few minutes of silence before next nucleating. This phenomenon may be due to the enhancement of convection induced by boiling, which leads to the thinning of the boundary layer and inhibits nucleation.…”
Section: Heterogeneous Nucleationmentioning
confidence: 99%